Effects of precooling treatments of cosmos caudatus (ulam raja) methanolic extract on total flavonoid content and free radical scavenging activity / Noor Shahimah Mohd Shah - Mohd Shah, Noor Shahimah (Faculty of Health Sciences, 2015)
Cosmos caudatus (ulam raja) is one of the herbs that are consumed by several communities in Malaysia especially the Malay community that acts as a natural antioxidant. Many studies had been conducted in order to determine antioxidant activities of this plant. However, there still lacking of information regarding the effect of pre-cooling treatment in the total flavonoid content and antioxidant activities of C caudatus. The objective of this study is to determine the effect of precooling treatment on the total flavonoid content and antioxidant activity of C. caudatus. A methanolic extract of C. caudatus was analysed using aluminium chloride colorimetric assay for determination of total flavonoid content (TFC) and 1, l-diphenyl-2-picylhydrazyl free radical scavenging assay (DPPH) was used to determine the antioxidant activity. The result showed the total flavonoid content at temperature -20°C, 4°C and 25°C were 326.07±0.40, 299.47±1.15 and 208.03±0.40 mg QE/100 g dry weight respectively. There were significant differences (P < 0.05) between the temperatures at -20°C, 4°C and 25°C for the total flavonoid contents. While the antioxidant activity at temperature -20°C, 4°C and 25°C were 77.17±0.03%, 84.21 ±0.12% and 90.58±0.00% respectively. There were significant differences (P < 0.05) between the temperatures at -20°C, 4°C and 25°C for the antioxidant activities. As the conclusion freezing and refrigeration temperature does not significantly affect antioxidant activity. Total flavonoid content is not the main contributor of the antioxidant activity in C caudatus as reflected by the negative correlation result (R* = -0.994) between the two suggestive of other components in C caudatus contributing to the high antioxidant activity.